(untitled) (Altre Modernità, 2023)
Focusing on the Latin authors Cicero (I century BC) and, to a lesser extent, Symmachus (IV-V centuries AD), this contribution explores the relationship between the value concept of humanitas, amicitia understood in its sociopolitical dimension, and the epistolary exchange. In particular, it aims to show that non unlike a virus like SARS-CoV-2, the idea(l) of humanitas can be infective – although infective is to be taken in a positive way on this occasion – and that it too is influenced by innate characteristics in much the same way as medicine defines congenital components. Moreover, it will emerge that humanitas also has a preferential means of propagation, namely letters, which at the same time prove to be an ideal serological test or molecular swab.